Status epilepticus: Having treatment paradigms in place in Neurosurgical settings - Amit Arora; Manjari Tripathi (Indian Journal of Neurosurgery)
Status epilepticus (SE) is an emergency situation, which needs immediate and prompt treatment. Lack of early treatment often leads to permanent neuronal damage and poor long-term neurological outcome. Among the known neurosurgical causes of SE are central nervous system (CNS) tumors, subarachnoid and intracerebral hemorrhage (ICH), head trauma and post-operative states. Given the frequency of SE events in neurosurgical wards, it is essential that the neurosurgical teams and intensive care unit staff are adequately sensitized to the prompt detection and management of SE. Uniform, easily understandable and logical algorithms are needed as part of care pathways to enable satisfactory management. Such measures are imperative in improving long-term patient outcome.